Multifractal and optical bandgap characterization of Ta2O5 thin films deposited by electron gun method - Shakoury, Reza; Rezaee, Sahar; Mwema, Fredrick; Luna, Carlos; Ghosh, Koushik; Jurečka, Stanislav; Ţălu, Ştefan; Arman, Ali; Grayeli Korpi, Alireza (Optical and quantum electronics, 2020)
The micromorphology of tantalum pentoxide (Ta 2 O 5 ) thin films, deposited on glass substrates by electron gun method, has been analyzed using atomic force microscopy (AFM), UV–Vis–NIR spectrophotometry and multifractal analyses. Two samples were grown at basic pressure of 7 × 10 −6 mbar, work pressures of 1.3 × 10 −4 and 2.0 × 10 −4 mbar, and thicknesses of 0.38 μm and 0.39 μm, respectively. Subsequently, these samples were annealed at 300 °C for 2 h. The physical, structural and optical analyses were investigated by spectroscopic ellipsometry, spectrophotometry and AFM. The measured transmittance spectra were studied based on the Swanepoel method, whose results also yielded to the estimation of the film thickness and the refractive index. Finally, Ta 2 O 5 thin films were characterized by AFM measurements and multifractal analyses for an accurate description of the 3-D surface microtexture features. The fractal examinations of the samples revealed that these microstructures exhibit multifractal characteristics. Essential parameters that characterized the thin films were compared and discussed thoroughly.